ARTIFICIAL INTELLIGENCE AND THE PROMOTION OF DIVERSITY AND INCLUSION (KECERDASAN BUATAN DAN PROMOSI KEANEKARAGAMAN DAN INKLUSI) - Junianto Karsudjono, Anthonius; Rahmayanti, Nida Putri (STIE Mahardhika, 2025)
This research is about Artificial Intelligence and the Promotion of Diversity and Inclusion. This research measures the relationship between variables, namely: promotion of diversity, promotion of diversity and inclusion towards increasing inclusion and diversity through the role of artificial intelligence. Obyek penelitian ini di kota-kota sekitar Banjarbaru dan sebagian Jawa Timur. Jumlah sample dalam penelitian ini adalah sebanyak 310 orang. In this research, the PLS-SEM approach is used, namely There are two stages of evaluation of the measurement model used, namely the measurement model (outer model) and the structural model (inner model). In testing this research, two stages were used, namely the outer model and the inner model and the statistical tool used is SmartPls version 3. The results of the research are 1. The diversity promotion variable has a positive effect on Artificial Intelligence. 2. Diversity and Inclusion variables for employees have a positive effect on Artificial Intelligence. 3. The diversity promotion variable has a positive effect on Inclusion and Increasing Diversity. 4. Diversity and Inclusion Variables for Employees have a positive effect on Increasing Inclusion and Diversity. 5. Artificial Intelligence variables have a positive effect on Inclusion and Increased Diversity. 6. The diversity promotion variable has a positive effect on Inclusion and Increasing Diversity through the Artificial Intelligence variable as an intervening variable. 7. Diversity and Inclusion variables have a positive effect on Inclusion and Increased Diversity through the Artificial Intelligence variable as an intervening variable. From this research, it is recommended that AI can play a role in increasing diversity and inclusion in the workplace.